Decalogue for an Effective Teaching - F. Javier Murillo; Cynthia Martinez Garrido; Reyes Hernandez-Castilla (Universidad Autónoma de Madrid, 2016)
One of the most interesting lines of research to improve the quality of education is one that seeks to find what classroom factors that contribute most effectively to help students learn and how develop educational activities in the classroom it achieves its objectives. This article presents a review of lessons learned from the thousands of research conducted worldwide on effective teaching. The main features have being gathered according to international research to define effective teaching in ten major factors: Involvement and teacher's commitment, Classroom climate, High expectations and self-structured lessons, Interactive teaching, Attention to diversity, Proper time management, Organization and classroom management, Use of teaching resources and, Evaluation, monitoring and continuous feedback; Thus, we have developed what it could be a "Decalogue for effective teaching."